Laboratory Empires: How Diseases and Environmental History modify our perception of the History of Colonisation - (:unkn) unknown (My University, 2021)
This paper will discuss the causes, consequences and management of the sanitary aspects of colonial expansion and rule in two different parts of the former British colonial empire. It will first address the role played by tropical diseases such as yellow fever in the conquest of the regions and islands surrounding the Caribbean Sea: how did environmental conditions enable historians to write innovative narratives of past events that take into account trans-disciplinary developments in the field of Environmental History? Second, it will examine the question of whether British colonial power contributed to the spread of endemic and epidemic diseases across the African continent, with the British fight against trypanosomiasis in Eastern and Southern Africa studied as an example. In doing so, this discussion will evaluate the impact of the solutions implemented to help the development of farming industries and to further their integration in a vast global and imperial trade network. For each of these experimental situations, the paper will try to determine the causes of these new developments and evaluate the significance of the social and environmental consequences arising from this unprecedented connection of different parts of the world and the gradual building of an imperial trade network on a global scale. It will also recall the various solutions implemented in order to solve the challenge posed by the transformation of local tropical diseases into global pandemics in the context of the expansion of a global trade and communication network.
Keywords: African Research